2015
DOI: 10.1186/s40712-015-0030-2
|View full text |Cite
|
Sign up to set email alerts
|

Recycled-copper-filled epoxy composites: the effect of mixed particle size

Abstract: Background: The effect of mixed size of recycled-copper-filled epoxy composites on mechanical, electrical, thermal and physical properties was investigated.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
4
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(5 citation statements)
references
References 32 publications
1
4
0
Order By: Relevance
“…The synergic effects of particle stiffness and ductility enhanced the flexural strength and modulus of the composites. Similar explanation has been made by [8]. The strengthening of the developed polymeric composites due to particle addition to the matrix is ascribed to craze formation during the flexural loading at the bending region.…”
Section: Flexural Properties Of Epoxy Aluminium Compositessupporting
confidence: 79%
See 1 more Smart Citation
“…The synergic effects of particle stiffness and ductility enhanced the flexural strength and modulus of the composites. Similar explanation has been made by [8]. The strengthening of the developed polymeric composites due to particle addition to the matrix is ascribed to craze formation during the flexural loading at the bending region.…”
Section: Flexural Properties Of Epoxy Aluminium Compositessupporting
confidence: 79%
“…Polymers are soft, light and resistant to chemical attack but their low mechanical properties limit their applications in engineering structures [6]. In developing polymeric composites, attempt to improve mechanical properties of polymers; conventional aramid, glass, carbon and natural bamboo, coconut, palm kernel, bagasse fibres have been used [7,8]. Among polymers is epoxy resin which has a good thermal stability, low shrinkage on curing and has been used as a matrix for developing high performance composites for engineering applications [9].…”
Section: Introductionmentioning
confidence: 99%
“…Besides, the use of waste products and waste materials as polymer raw materials will contribute to even greater cost reduction, and most importantly, a solution to the number of acute environmental and socio-economic problems. This will also expand their possible recycling and reuse in the form of high-tech metal-filled polymer composites [21][22][23].…”
Section: Introductionmentioning
confidence: 99%
“…The result showed that the electrical and thermal characteristics enhanced with adding copper powder while, the mechanical properties decreased compared with pure polyethylene matrix. Pargi et al [15] investigated the influence of mixed copper particle size filled epoxy composites on the thermal, electrical, and mechanical characteristics. The result showed enhancement in overall characteristics of epoxy composites filled with copper particles.…”
Section: Introductionmentioning
confidence: 99%